Pharmacological approaches in the treatment of autism: a narrative review - Medeiros, Gabriela Muro; Sepulveda, Mariana Marques; Gentile, João Kleber de; Braga, Alfésio Luís Ferreira (Brazilian Journal of Case Reports, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in communication and social interaction and by the presence of repetitive and restricted behaviors. To review the literature on drug interventions in the treatment of ASD in children and adolescents. Narrative review conducted at a university in São Paulo, Brazil. Search of the literature of studies published from 2005 to 2022, in Portuguese, English and Spanish, in the SciELO, PubMed, SCOPUS, LILACS and TripDatabase databases. Risperidone alone improved stereotyped patterns of behavior. Associations with aripiprazole or galantamine reduced irritability and managing the behavioral symptoms, respectively. Ginkgo biloba, associated to risperidone, led to an improvement in the Aberrant Behavior Checklist-Community (ABC-C) subscales scores. The association with sulforaphane exhibited a greater improvement in irritability and hyperactivity/noncompliance scores. Omega-3s reduced gesture use and hyperactivity. Bumetanide reduced restricted interests and repetitive behavior compared to placebo. Intranasal oxytocin improved social skills. The AB-2004 showed improvement in behavioral endpoints, especially anxiety and irritability. Folinic acid improved verbal communication in non-syndromic ASD children. Prednisolone increased language scores. There is not a drug that treats all of them and the possibility of significant adverse effects must be adjusted according to the symptoms and clinical response.